Ametsuchi - Kawauchi, Rinko (New York, NY : Aperture Foundation, 2013)
Ametsuchi, is comprised of two Japanese characters meaning heaven and earth and is taken from the title of one of the oldest pangrams in Japanes - a chant in which each character of the Japanese syllabary is used.
boek
Keywords: Kawauchi, Rinko